EFFETS DE LA BIOMASSE ET DU COMPOST DE CASSIA OCCIDENTALIS L. SUR LA CROISSANCE EN HAUTEUR, LE RENDEMENT DU MAÏS (ZEA MAYS L.) ET LA TENEUR EN NPK D’UN SOL DÉGRADÉ EN STATION EXPÉRIMENTALE - Outéndé Toundou; Koffi Tozo; Kokou A. A. Amouzouvi; Lankondjoa Kolani; Gado Tchangbedji; Koffi Kili; Baba Gnon (European Scientific Journal, ESJ, 2014)
In this study, we tested the possibility of using C. occidentalis L., as green manure, compost and improved fallows to regenerate degraded soil. Methods: In some plots of the degraded soil, we buried biomass of Cassia occidentalis and others were either treated with compost of Cassia with or without ash, or performed from improved fallow of Cassia. All the treated plots were then used for a maize culture (Zea mays, var IKENE). The experimental design was that of Fischer with 9 treatments and 4 replicates per treatment. Results: The study showed that the best values for plant height were scored for the plots treated with the green manure of Cassia and the plots treated with compost +ash. The greatest values of grain yields and mass of 1000 grains were obtained for the plots treated with green manure of Cassia and those treated with compost without ash. About the fertility of the treated soil after harversting, the highest values for nitrogen content were scored for the plots treated with compost of cassia containing or not ash whereas highest values for phosphorus content were obtained for the plots treated with the green manure of Cassia. For the the potassium content, the bests results were scored for the plots treated with composts containing ash. Conclusion: these results showed that C. Occidentalis was a convenient source for minerals and allowed us to think that this leguminous could be used in degraded soils restoration programs